(untitled) (Research, Society and Development, 2021)
The objective of this study was to determine the dry matter, pH and volatilized ammonia of fresh waste from commercial laying hens treated or not with different additives. The experimental design was randomized in factorial scheme 4 x 5 (4 types of waste x 5 periods) and four replications. It has assessed: fresh waste (DF), DF + calcium oxide (500 g.m2), DF + calcium sulfate (40% of bed weight) and DF + diatomaceum earth (200 g.m2), in periods 0 (before application) and 4, 8, 12 and 16 days after application. It was observed that the waste treated with calcium oxide and sulfate showed higher dry matter contents compared to the control. There was a quadratic behavior for the dry matter content as a function of the period. The pH of fresh waste and waste treated with diatomaceous earth did not change during the periods analyzed, however, the waste treated with oxide and calcium sulfate showed quadratic behavior over the 16 days of evaluation for this variable. For volatilized ammonia, the waste submitted to calcium sulfate and diatomaceous earth did not differ from the control until 12 days after application. However, the addition of calcium oxide in the wastes promoted a quadratic effect for this variable throughout the experimental period. The use of calcium sulfate to laying hens waste reduces moisture and pH and inhibits ammonia volatilization for up to 12 days. After this period a new application is recommended.